Clinical, Laboratory and Neuroimaging of Acquired Demyelinating Syndrome of the Children Admitted in a Tertiary Care Hospital in Bangladesh (Journal of Bangladesh College of Physicians and Surgeons, 2025)
Background: Acquired demyelinating syndrome (ADS) are autoimmune inflammatory disorder affecting the white matter of brain, optic nerve and spinal cord, and it has long been unrecognized. Early diagnosis and proper management slow the disease progression and reduce mortality and morbidity.Objective: To find out the clinical, laboratory and neuroimaging patterns of ADS in children in Bangladesh.Materials and Methods: A cross-sectional study was conducted from July 2020 to January 2021 in the Department of Pediatric Neurology, National Institute of Neuroscience and Hospital, including 37 children